A scenario of healthcare waste management in chikkaballapura, karnataka - Jiban Singh, M; Venkatesh Murthy, N; Ranga Swamy, H.V (Health, Safety and Environment, 2020)
In Chikkaballapura, most of the doctors won't go through the Bio-Medical Waste (Management and Handling) Rules, 1998 once in their life and Guideline on Bio-Medical Waste Management issued by KHSDRP. According to consequence, only educated and punishing regarding healthcare waste management programme cannot be successfully implemented without the good Samskar (honesty, enthusiasm, dedication, self-motivation, cooperation and the participation) of all sections of the workers of healthcare centers. If the present generation wants to protect our future environment and health of the community, we must sense us to this important issue not only in the curiosity. Wastes from the 30 PHCs, 1 CHC, 5 THs and 1 DH in the district is being collected, transported, treated and disposed by CBMWTF. But due to the lack of common sense and irregularity of BMWCTF healthcare waste is unable to collect and manage properly in the HCFs. Generated wastes from remaining 25 PCHs are being disposed in DBPs and SPs and LDUs provided within the premises, but due to lack of Operation Theater (OT), Laboratory facilities, Healthcare building facility under the construction as well as shifting to new building, 37.09% of the LDUs in HCFs were not working and not installed.